Risk assessment in the prevention of violent extremism and terrorism: Theoretical and applied application of tools - Kržalić, Armin; Plevljak, Benjamin (Crisis Management Days, 2024)
A violence risk assessment has been used for decades by security agencies as an important tool in assessing future violence. The currently available risk assessment protocols have questionable relevance for the assessment of violent extremism and terrorism because the factors used to assess risk are not linked to the background and motivation of this group of violent actors. This is why there is a need for a relevant risk assessment tool for the population of violent and ideologically motivated extremists. The new SPJ Protocol - Structured Professional Judgment and Violent Extremist Risk Assessment or VERA- are designed for people with a history of violent extremist violence or who have been convicted of such offenses. The paper aims to identify and compare the specific characteristics of risk assessment tools in the prevention of violent extremism in six European countries (Netherlands, Belgium, Italy, Kosovo, North Macedonia and Bosnia and Herzegovina) and to highlight significant differences between the tools themselves and their application. The results show that Belgium and the Netherlands have the best practice of applying risk assessment tools, and SPJ-Structured Professional Judgment in both cases can be an excellent example for others, at least as a basis for designing new instruments and tools. For the context of Bosnia and Herzegovina, it might be useful to try the following tools: SQAT, HCR-20 and VERA-2R.